Safeguarding the intangible heritage during armed conflict - خلف حسام عبد الامير; الاركوازي محمد اسماعيل (Journal of Legal Sciences, 2021)
There are many mechanisms that can be used to safeguard intangible cultural heritage during armed conflict, either indirectly through the international texts of armed conflict, from the perspective of protecting customs, traditions and religious beliefs, or directly by incorporating this heritage into UNESCO regulations. This heritage can also be preserved from the concept of human rights principles that can be applied during armed conflicts. Moreover, the best way to preserve this heritage is to prosecute and punish violators of the provisions of safeguarding this heritage, whether in national criminal courts or international criminal courts.